ANALISIS KEUNGGULAN BERSAING (COMPETITIVE ADVANTAGE) DALAM PERSPEKTIF EKONOMI ISLAM - Santoso, Haris (Islamic Economics Program, Faculty of Islamic Economics and Business, 2022)
In the business world, especially in the supermarket business, competition cannot be separated, the number of supermarkets that are established will make business competition increasingly tight in the supermarket industry. Competitive advantage is now the spearhead of a business. PB Supermarket is one of the supermarkets that is included in the minimarket category which is equivalent to Alfamart, Indomart and other minimarkets in Metro City. This study aims to determine the steps of PB Supermarkets in applying their competitive advantage. After knowing the steps of PB Supermarkets in implementing competitive advantage, it will be analyzed in the perspective of Islamic economics. Judging from its type, this research is a descriptive field research. In the data collection method, researchers used interviews or interviews, documentation, and observation. As for the results of this study, namely that PB Supermarkets have a high competitive industrial environment, it can be seen that there are many supermarkets standing in Metro City. Based on the SWOT analysis PB Swalayan also has good strengths and opportunities to cover weaknesses and face threats. To face a high competitive environment, PB Swalayan applies competitive advantage in the form of improving service quality, providing goods that are needed by the community or a complete target market, and conducting promotional programs in the form of prize draws, and what is prioritized in PB Swalayan's competitive advantage is lower prices compared to its competitors. The competitive advantage applied by PB Supermarkets is in accordance with Islamic Economics or Islamic business ethics, namely the principles of honesty, trustworthiness, tolerance, and fulfilling contracts and promises, and not using methods that are prohibited by religion.